Insecticide resistance in the blue tick, Boophilus Decoloratus Koch, in South Africa - Whitehead, G B (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1960)
The work described in this dissertation was undertaken in an attempt to obtain a better understanding of the causes and relationships of insecticide resistance in Blue Tick, Boophilus decoloratus Koch, which has become an acute problem in some localities of the country. The work was undertaken at the Research Department of African Explosives and Chemical Industries Limited over a period of six years from 1953 to 1958. An attempt has been made to keep up to date with the published literature on the various aspects of these investigations up until the end of 1958. Information gained from the literature subsequent to end of 1958 has been made use of but it has not been possible for a number of reasons to follow all recent developments in the various aspects of insecticide resistance published during 1959. In the execution of this work assistance has been obtained from colleagues better equipped in the field of organic chemistry, biochemistry and statistics, than the author. Where information so gained has been used it has been duly acknowledged. Considerable assistance was rendered by laboratory assistants who were responsible for performing the considerable amount of routine collection, breeding and testing of the biological material. The blue tick is not a convenient experimental organism for studies on insecticide resistance. Even with the best facilities the tick cannot be bred satisfactorily and in consequence all supplies had to be collected from naturally-occurring populations. Although this had decided advantages in some aspects of the work, a great deal of useful information might have been obtained if certain strains of ticks could have been maintained. The lack of a standard sensitive reference strain has been a considerable disadvantage which could not be overcome and which has influenced the manner in which this work has been carried out. Because the tick could not be bred artificially the work could only be undertaken with unfed larvae and fully engorged adult females . Larvae are extremely small and in consequence could only be handled in batches while the fully engorged female is sluggish and contains a large quantity of semi-digested mammalian blood which invariably interfered with chemical or biochemical studies.
Keywords: Uncatalogued